Delayed Auditory Evoked Responses in Autism Spectrum Disorder across the Life Span - Matsuzaki, Junko; Ku, Matthew; Dipiero, Marissa; Chiang, Taylor; Saby, Joni; Blaskey, Lisa; Kuschner, Emily S; Kim, Mina; Berman, Jeffrey I; Bloy, Luke; Chen, Yu-Han; Dell, John; et al. (Developmental neuroscience, 2019)
The M50 and M100 auditory evoked responses reflect early auditory processes in the primary/secondary auditory cortex. Although previous M50 and M100 studies have been conducted on individuals with autism spectrum disorder (ASD) and indicate disruption of encoding simple sensory information, analogous investigations of the neural correlates of auditory processing through development from children into adults are very limited. Magnetoencephalography was used to record signals arising from the left and right superior temporal gyrus during auditory presentation of tones to children/adolescents and adults with ASD as well as typically developing (TD) controls. One hundred and thirty-two participants (aged 6-42 years) were included into the final analyses (children/adolescents: TD, n = 36, 9.21 ± 1.6 years; ASD, n = 58, 10.07 ± 2.38 years; adults: TD, n = 19, 26.97 ± 1.29 years; ASD, n = 19, 23.80 ± 6.26 years). There were main effects of group on M50 and M100 latency (p < 0.001) over hemisphere and frequency. Delayed M50 and M100 latencies were found in participants with ASD compared to the TD group, and earlier M50 and M100 latencies were associated with increased age. Furthermore, there was a statistically significant association between language ability and both M50 and M100 latencies. Importantly, differences in M50 and M100 latencies between TD and ASD cohorts, often reported in children, persisted into adulthood, with no evidence supporting latency convergence.